2009
DOI: 10.1089/ars.2008.2318
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer Agent Chaetocin Is a Competitive Substrate and Inhibitor of Thioredoxin Reductase

Abstract: We recently reported that the antineoplastic thiodioxopiperazine natural product chaetocin potently induces cellular oxidative stress, thus selectively killing cancer cells. In pursuit of underlying molecular mechanisms, we now report that chaetocin is a competitive and selective substrate for the oxidative stress mitigation enzyme thioredoxin reductase-1 (TrxR1) with lower K m than the TrxR1 native substrate thioredoxin (Trx; chaetocin K m ¼ 4.6 ± 0.6 mM, Trx K m ¼ 104.7 ± 26 mM), thereby attenuating reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 25 publications
7
84
0
Order By: Relevance
“…The fact that (i) chaetocin has been reported to be a competitive inhibitor of thioredoxine (Trx) for Trx reductase activity (TrxR1); 43 (ii) TrxR/Trx pathway is central in limiting ROS production; and (iii) chaetocin may exert anticancer effects via ROS generation (Isham et al 19 and this study) indicates that TrxR1 inhibition by chaetocin may at least partially explain ROS-mediated anticancer activity. However, this hypothesis does not exclude the role of the direct inhibition of SUV39H1 in chaetocin-induced apoptosis.…”
Section: Discussionmentioning
confidence: 68%
“…The fact that (i) chaetocin has been reported to be a competitive inhibitor of thioredoxine (Trx) for Trx reductase activity (TrxR1); 43 (ii) TrxR/Trx pathway is central in limiting ROS production; and (iii) chaetocin may exert anticancer effects via ROS generation (Isham et al 19 and this study) indicates that TrxR1 inhibition by chaetocin may at least partially explain ROS-mediated anticancer activity. However, this hypothesis does not exclude the role of the direct inhibition of SUV39H1 in chaetocin-induced apoptosis.…”
Section: Discussionmentioning
confidence: 68%
“…We first examined whether Suv39H1, oxidative stress, or thioredoxin reductase-1 is involved in HIF-1a suppression. [12][13][14] However, HIF-1a expression and the chaetocin effect occurred regardless of these factors (Fig. 4A-C).…”
Section: Resultsmentioning
confidence: 87%
“…13 Mechanistically, it was proposed that chaetocin produces oxidative damage in myeloma cells by inhibiting the antioxidant enzyme thioredoxin reductase. 14 However, little is known about the effects of chaetocin on solid tumors, and thus we tested the anticancer activity of chaetocin against solid tumors. Here we demonstrated that chaetocin has antiangiogenic and anticancer activities in hepatoma and fibrosarcoma grafts, and that these actions of chaetocin are due to HIF-1a down-regulation caused by the deregulation of HIF-1a premessenger RNA (pre-mRNA) splicing.…”
mentioning
confidence: 99%
“…To target other classes of chromatin-modifying enzymes, compounds were chosen that have mostly been previously described: as HKMT inhibitors, we used chaetocin (16), a nonspecific compound originally described as selective for SU(VAR)3-9 and later shown to inhibit G9a (17) and thioredoxin reductase (18); BIX-01294 (19,20), a G9a/GLP-specific compound, and its active analog BRD-K62233722. DNMT inhibitors were 5-azadeoxycytidine (decitabine) (21), zebularine (22), and RG-0108 (23).…”
Section: Resultsmentioning
confidence: 99%